Physiological and Proteomic Analyses of Drought Stress Response in Holm Oak Provenances - Valero-Galvàn, José; González-Fernández, Raquel; Navarro-Cerrillo, Rafael Maria; Gil-Pelegrín, Eustaquio; Jorrín-Novo, Jesús V (Journal of Proteome Research, 2013)
Responses to drought stress by water withholding have been studied in 1 year old Holm oak (Quercus ilex subsp. ballota [Desf.] Samp.) seedlings from seven provenances from Andalusia (southern Spain). Several physiological parameters, including predawn xylem water potentials and relative water content in soil, roots, and leaves as well as maximum quantum efficiency and yield of PSII were evaluated for 28 days in both irrigated and nonirrigated seedlings. The leaf proteome map of the two provenances that show the extreme responses (Seville, GSE, is the most susceptible, while Almer??a, SSA, is the least susceptible) was obtained. Statistically significant variable spots among provenances and treatments were subjected to MALDI-TOF/TOF-MS/MS analysis for protein identification. In response to drought stress, ?12.4% of the reproducible spots varied significantly depending on the treatment and the population. These variable proteins were mainly chloroplastic and belonged to the metabolism and defense/stress functional categories. The 2-DE protein profile of nonirrigated seedlings was similar in both provenances. Physiological and proteomics data were generally in good agreement. The general trend was a decrease in protein abundance upon water withholding in both provenances, mainly in those involved in ATP synthesis and photosynthesis. This decrease, moreover, was most marked in the most susceptible population compared with the less susceptible one.
From Duplicate 2 (Physiological and Proteomic Analyses of Drought Stress Response in Holm Oak Provenances - Valero-Galván, José; González-Fernández, Raquel; Navarro-Cerrillo, Rafael Maria; Gil-Pelegrín, Eustaquio; Jorrín-Novo, Jesús V)
Keywords: Analysis of Variance; biomass; Chlorophyll ﬂuorescence; drought stress in Holm oak; Droughts; Electrophoresis; Gel; Gene Expression Regulation; Holm oak proteomics; Physiological; Physiological: genetics; Physiological: physiology; Plant; Plant Leaves; Plant Leaves: genetics; Plant Leaves: metabolism; Plant Proteins; Plant Proteins: metabolism; Plant: genetics; Plant: physiology; Proteomics; Proteomics: methods; Quercus; Quercus ilex; Quercus: genetics; Quercus: metabolism; Quercus: physiology; Seedling; Seedling: growth & development; Seedling: metabolism; Spain; Stress; Tandem mass spectrometry; Two-Dimensional; water potential

Direct and indirect landscape effects on Quercus ilex regeneration in heterogeneous environments. - Puerta-Piñero, Carolina; Pino, Joan; Gómez, José María (Oecologia, 2012)
Understanding how plant-animal interactions shape plant regeneration is traditionally examined at local scales. In contrast, landscape ecologists working at regional scales often have to infer the mechanisms underlying vegetation patterns. In this study, we empirically explored how landscape attributes (patch connectivity, size, shape, irradiance, slope, and elevation) influence biotic interactions in 1- and 2-year seedlings and saplings of Quercus ilex. We combined field data and GIS-based information under a set of five connectivity scenarios, presuming low, intermediate, and long-distance seed dispersal. Our study emphasizes that landscape, apart from its direct effects on plants, plays a key, albeit indirect, role in plant demography through its effects on seed dispersers and predators. Moreover, the effects of landscape on recruitment differed between plant life stages. One-year seedlings and saplings appear to depend more on plant-animal interactions, while 2-year seedlings depend more on irradiance. Differences in patch connectivity resulted in direct and indirect effects on biotic interactions, which, in turn, produced contrasting positive and negative effects on regeneration at different stages of the life cycle. While jays and wild boars seem crucial to all life stages and most of the connectivity scenarios, rodents and herbivores affected only 1-year seedlings and saplings, respectively, and only a few of the connectivity scenarios. By simultaneously including an ensemble of explanatory factors, our study emphasizes that regeneration depends on a set of key drivers, both abiotic (i.e. irradiance) and biotic (i.e. jays and wild boars), whose effects are greatly modulated by landscape traits.
Keywords: Animals; Ecosystem; irradiance; landscape connectivity; Life Cycle Stages; Mediterranean; Passeriformes; Plant Dispersal; Plant–animal interactions; Quercus; Quercus: growth & development; Recruitment; Seedling; Seedling: growth & development; Sus scrofa

Spatial patterns of soil pathogens in declining Mediterranean forests: implications for tree species regeneration. - Gómez-Aparicio, LORENA; Ibáñez, Beatriz; Serrano, María S.; De Vita, Paolo; Avila, José M.; Pérez-Ramos, Ignacio M.; García, Luis V.; Esperanza Sánchez, M.; Marañón, Teodoro (The New phytologist, 2012)
Soil-borne pathogens are a key component of the belowground community because of the significance of their ecological and socio-economic impacts. However, very little is known about the complexity of their distribution patterns in natural systems. Here, we explored the patterns, causes and ecological consequences of spatial variability in pathogen abundance in Mediterranean forests affected by oak decline. We used spatially explicit neighborhood models to predict the abundance of soil-borne pathogen species (Phytophthora cinnamomi, Pythium spiculum and Pythium spp.) as a function of local abiotic conditions (soil texture) and the characteristics of the tree and shrub neighborhoods (species composition, size and health status). The implications of pathogen abundance for tree seedling performance were explored by conducting a sowing experiment in the same locations in which pathogen abundance was quantified. Pathogen abundance in the forest soil was not randomly distributed, but exhibited spatially predictable patterns influenced by both abiotic and, particularly, biotic factors (tree and shrub species). Pathogen abundance reduced seedling emergence and survival, but not in all sites or tree species. Our findings suggest that heterogeneous spatial patterns of pathogen abundance at fine spatial scale can be important for the dynamics and restoration of declining Mediterranean forests.
The following values have no corresponding Zotero field: accession-num: 22428751
Keywords: Biological; Forest decline; Host-Pathogen Interactions; Mediterranean Region; Models; neighborhood models; Phytophthora; Phytophthora: physiology; Pythium; Pythium: physiology; Quercus; Quercus suber; Quercus: microbiology; regeneration dynamics; Seedling; Seedling: microbiology; Soil Microbiology; soil texture; soil-borne pathogens; species coexistence

Sporadic rainy events are more critical than increasing of drought intensity for woody species recruitment in a Mediterranean community. - Matías, Luis; Zamora, Regino; Castro, Jorge (Oecologia, 2012)
The understanding of the impact of extreme climatic events under a global climate change scenario is crucial for the accurate forecast of future plant community dynamics. We have experimentally assessed the effect of drier and wetter summer conditions on the recruitment probabilities and the growth of seedlings from eight woody species representative of the most important functional groups in the community, pioneer shrubs, mid-successional shrubs and trees, across the main habitats in the study area (open habitat, shrubland, and forest). Our hypothesis proposes that wet summer conditions would represent a good opportunity for tree species regeneration, enhancing both forest maintenance and expansion. A drier summer scenario, on the other hand, would limit forest regeneration, and probably hinder the colonization of nearby habitats. We found a habitat effect on the emergence, survival, and final biomass, whereas different climate scenarios affected seedling survival and biomass. A wet summer boosted growth and survival, whereas greater drought reduced survival only in some cases. These results were modulated by the habitat type. Overall, shrub species presented higher survival and growth and were less affected by more severe drought, whereas some tree species proved to be extremely dependent on wet summer conditions. We conclude that the reduction in frequency of wet summers predicted for the coming decades in Mediterranean areas will have greater consequences for species recruitment than will increased drought. The different response of the species from the various functional groups has the potential to alter the composition and dominance of future plant communities.
Keywords: Angiosperms; Angiosperms: growth & development; climate change; Droughts; Ecosystem; Mediterranean Region; Rain; rainfall variability; Recruitment; Seedling; Seedling: growth & development; Spain; summer drought; Vegetation dynamics

Artificial regeneration with Quercus ilex L. and Quercus suber L. by direct seeding and planting in southern Spain - González-Rodríguez, Victoria; Navarro-Cerrillo, Rafael M.; Villar, Rafael (Annals of Forest Science, 2011)
& Introduction The limited ability of Quercus species to regenerate naturally in Mediterranean forests has led to the development of various artificial regeneration methods; however, there is no general consensus as to what specific method is the best one for this purpose. & Material and methods In this work, we assessed morphology, growth and survival of two Quercus species (Quercus ilex ssp. ballota and Quercus suber) using two different methods of artificial regeneration (viz. direct seeding and planting) and two seedling ages (1-year-old seedlings and 3-year-old seedlings) in southern Spain. & Results and discussion The 1-year-old seedlings of both species were found to exhibit the highest survival percentages and direct-seeded plants intermediate survival values. For direct-seeded plants, seed mass was found to have a significantly positive effect on the establishment success in both species. No clear-cut trend in survival was detected in the 3- year-old seedlings. The survival of the 3-year-old Q. suber seedlings and the direct-seeded plants was similar, but not in Q. ilex, where the survival of the 3-year-old seedlings was the lowest. The latter result may have been a consequence of cultivation in smaller containers leading to root deformation and limiting plant access to water. Differences in survival could not be ascribed to morphological and growth variables or stomatal conductance. & Conclusion Based on the results, all three artificial regeneration methods can be similarly effective provided appropriate nursery cultivation conditions are used and seeds are protected against predators, the best choice in each case being dictated by the particular restoration goals.
Keywords: artificial regeneration; Nursery; oak; Seedling; sowing

Changes in water content and distribution in Quercus ilex leaves during progressive drought assessed by in vivo 1H magnetic resonance imaging. - Sardans, Jordi; Penuelas, Josep; Lope-Piedrafita, Silvia (BMC plant biology, 2010)
Drought is a common stressor in many regions of the world and current climatic global circulation models predict further increases in warming and drought in the coming decades in several of these regions, such as the Mediterranean basin. The changes in leaf water content, distribution and dynamics in plant tissues under different soil water availabilities are not well known. In order to fill this gap, in the present report we describe our study withholding the irrigation of the seedlings of Quercus ilex, the dominant tree species in the evergreen forests of many areas of the Mediterranean Basin. We have monitored the gradual changes in water content in the different leaf areas, in vivo and non-invasively, by 1H magnetic resonance imaging (MRI) using proton density weighted (rhow) images and spin-spin relaxation time (T2) maps.
From Duplicate 1 ( Changes in water content and distribution in Quercus ilex leaves during progressive drought assessed by in vivo 1H magnetic resonance imaging. - Sardans, Jordi; Peñuelas, Josep; Lope-Piedrafita, Silvia )
Keywords: Droughts; Magnetic Resonance Imaging; Physiological; Plant Leaves; Plant Leaves: metabolism; Quercus; Quercus: metabolism; Seedling; Seedling: metabolism; Soil; Soil: analysis; Stress; Time Factors; water; Water: metabolism (citation)

Remobilization of acorn nitrogen for seedling growth in holm oak (Quercus ilex), cultivated with contrasting nutrient availability. - Villar-Salvador, Pedro; Heredia, Norberto; Millard, Peter (Tree physiology, 2010)
The relative contribution of nitrogen (N) reserves from seeds or uptake by the roots to the growth and N content of young seedlings has received little attention. In this study, we investigated the contribution of N from the acorn or uptake by the roots to the N content of holm oak (Quercus ilex L.) seedlings and determined if remobilization of acorn N was affected by nutrient availability in the growing media. Q. ilex seedlings were cultivated for 3 months, until the end of the second shoot flush of growth, with three N fertilization rates: 8.6 mM N, 1.4 mM N or no fertilization. Fertilizer N was enriched in (15)N. Between 62 and 75% of the N contained in high and low fertilized seedlings, respectively, at the end of the second flush of growth was derived from the acorn. However, the dependence on acorn N was greater during the early root growth and first shoot flush of growth and decreased during the second shoot flush of growth, with root uptake contributing 32-54% of plant new N in this latter developmental stage in high and low fertilized plants, respectively. Fertilization rate did not affect the amount of N taken up during the earliest developmental stages, but it increased it during the second shoot flush of growth. Fertilization increased the mass of the shoot segment formed during the second shoot flush of growth and reduced the root mass, with no effect on whole plant growth. Remobilization of acorn N was faster in unfertilized plants than in fertilized plants. It is concluded that the holm oak seedlings depend greatly upon acorn N until the end of the second shoot flush of growth, that significant root N uptake starts at the beginning of the second shoot flush of growth and that acorn N remobilization is a plastic process that is accelerated under extremely low substratum nutrient content.
Keywords: germination; nitrogen; Nitrogen Isotopes; Nitrogen Isotopes: metabolism; Nitrogen: metabolism; Quercus; Quercus: growth & development; Quercus: metabolism; Seedling; Seedling: growth & development; Seedling: metabolism; Seeds; Seeds: metabolism; Soil

Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor (Tree Physiology, 2006)
Shade and irrigation are frequently used to increase the success of Mediterranean Quercus spp. plantations. However, there is controversy about the combined effects of these treatments on plant performance. We assessed the effects of two irradiances (full sunlight and moderate shade) and two summer watering regimes (high (daily) and low (alternate days)) on leaf and whole-plant traits of 1-year-old seedlings of Quercus coccifera, Q. ilex subsp. ballota and Q. faginea grown outdoors for 8.5 months. Leaf traits included measures of morphology, nitrogen concentration, gas exchange and photochemical efficiency, and measures of whole-plant traits included biomass allocation patterns, growth phenology, across-summer leaf area change and relative growth rate (RGR).Moderate shade reduced leaf mass per area, increased photochemical efficiency, maximum carbon assimilation rate (Amax) and allocation to leaves, and prolonged the growing period in one or more of the species. Daily watering in summer increased Amax of Q. ilex and prolonged the growing period of Q. ilex and Q. faginea. Both treatments tended to increase RGR. The effect of shade was greater in the low-watering regime than in the high-watering regime for two of the 15 studied traits, with treatment effects being independent for the remaining 13 traits. Leaf nitrogen and the ability to maintain leaf area after the arid period, rather than biomass allocation traits, explained the variation in seedling RGR. Trait responsiveness to the treatments was low and similar among species and between study scales, being unexpectedly low in Q. faginea leaves. This may be because selective pressures on leaf plasticity act differently in deciduous and evergreen species. We conclude that moderate shade and daily summer watering enhance the performance of Mediterranean Quercus seedlings through species-specific mechanisms.
From Duplicate 2 (Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor)
Keywords: Agriculture; Agriculture: methods; Analysis of Variance; biomass allocation; carbon assimilation rate; fluorescence; Mediterranean Region; Phenology; Phenotype; Plant Leaves; Plant Leaves: growth & development; Plant Shoots; Plant Shoots: physiology; Quercus; Quercus: drug effects; Quercus: growth & development; Quercus: physiology; Relative growth rate; Seedling; Seedling: drug effects; Seedling: physiology; water; Water: metabolism; Water: pharmacology

Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G.; Maestro, Melchor (Tree Physiology, 2006)
Shade and irrigation are frequently used to increase the success of Mediterranean Quercus spp. plantations. However, there is controversy about the combined effects of these treatments on plant performance. We assessed the effects of two irradiances (full sunlight and moderate shade) and two summer watering regimes (high (daily) and low (alternate days)) on leaf and whole-plant traits of 1-year-old seedlings of Quercus coccifera, Q. ilex subsp. ballota and Q. faginea grown outdoors for 8.5 months. Leaf traits included measures of morphology, nitrogen concentration, gas exchange and photochemical efficiency, and measures of whole-plant traits included biomass allocation patterns, growth phenology, across-summer leaf area change and relative growth rate (RGR).Moderate shade reduced leaf mass per area, increased photochemical efficiency, maximum carbon assimilation rate (Amax) and allocation to leaves, and prolonged the growing period in one or more of the species. Daily watering in summer increased Amax of Q. ilex and prolonged the growing period of Q. ilex and Q. faginea. Both treatments tended to increase RGR. The effect of shade was greater in the low-watering regime than in the high-watering regime for two of the 15 studied traits, with treatment effects being independent for the remaining 13 traits. Leaf nitrogen and the ability to maintain leaf area after the arid period, rather than biomass allocation traits, explained the variation in seedling RGR. Trait responsiveness to the treatments was low and similar among species and between study scales, being unexpectedly low in Q. faginea leaves. This may be because selective pressures on leaf plasticity act differently in deciduous and evergreen species. We conclude that moderate shade and daily summer watering enhance the performance of Mediterranean Quercus seedlings through species-specific mechanisms.
From Duplicate 2 (Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor)From Duplicate 2 (Interactive effects of shade and irrigation on the performance of seedlings of three Mediterranean Quercus species - Castro-Díez, Pilar; Navarro, Javier; Pintado, Ana; Sancho, Leopoldo G; Maestro, Melchor)The following values have no corresponding Zotero field: accession-num: 16356909
Keywords: Agriculture; Agriculture: methods; Analysis of Variance; biomass allocation; carbon assimilation rate; fluorescence; Mediterranean Region; Phenology; Phenotype; Plant Leaves; Plant Leaves: growth & development; Plant Shoots; Plant Shoots: physiology; Quercus; Quercus: drug effects; Quercus: growth & development; Quercus: physiology; Relative growth rate; Seedling; Seedling: drug effects; Seedling: physiology; water; Water: metabolism; Water: pharmacology

Variation in the holm oak leaf proteome at different plant developmental stages, between provenances and in response to drought stress. - Jorge, Inmaculada; Navarro, Rafael M; Lenz, Christof; Ariza, David; Jorrín, Jesús (Proteomics, 2006)
Major proteins of the holm oak leaf proteome have been previously identified using a combination of 2-DE, MS analysis and BLAST similarity search (Jorge et al., Proteomics 2005, 5, 222-234). That study, conducted with field samples from mature trees, revealed the existence of a great variability in the 2-DE protein map, with qualitative as well as quantitative changes, both analytical and biological. A similar study has been carried out with 2-year-old seedlings to analyze and study: (i) changes in the 2-DE protein profile at different tree developmental stages; (ii) the 2-DE protein map variability between three different Spanish provenances; and (iii) variations in the 2-DE protein profile in response to drought stress. Although the protein profile of leaves from seedlings and mature trees was fairly similar, the biological variance found was lower in the former. In the present study, new proteins have been identified. At least four different protein spots differentiated Spanish provenances, two of them identified as an ATP synthase alpha chain, and a 2,3-bisphosphoglycerate-independent phosphoglycerate mutase. Fourteen different protein spots were qualitatively variable between well-watered and drought-stressed seedlings, with some of them corresponding to enzymes of carbohydrate and protein metabolism. Data presented indicated the mobilization of storage proteins and carbohydrates, as well as photosynthesis inhibition under drought conditions.
Keywords: Dehydration; Dehydration: metabolism; Disasters; Electrophoresis, Gel, Two-Dimensional; Plant Leaves; Plant Leaves: metabolism; Proteome; Proteome: metabolism; Proteomics; Quercus; Quercus: embryology; Quercus: metabolism; Seedling; Seedling: metabolism

Establishment of co-existing Mediterranean tree species under a varying soil moisture regime - Lloret, Francisco; Penuelas, Josep; Ogaya, Romà (Journal of Vegetation Science, 2004)
We investigated the responses of two co-existing Mediterranean trees with different regeneration strategies (Phillyrea latifolia seedlings and Quercus ilex sprouts) to experimental drought below the forest canopy. We considered different recruitment stages and used leaf isotopic discrimination to estimate water use efficiency (WUE) and nitrogen availability and use. Drought decreased the emergence and survival of seedlings and sprouts. Survival and growth of older saplings were not influenced by drought. Seedling emergence of P. latifolia was higher than Q. ilex sprout production, but Q. ilex sprouts had higher survival and growth rates. These differences disappeared in the sapling stage. Carbon isotopic discrimination suggested that Q. ilex sprouts had higher WUE than P. latifolia seedlings. Drought increased WUE of recruits, particularly in Q. ilex. Water use regulation increased with ageing, particularly in P. latifolia. Q. ilex had higher δ15N values than P. latifolia; these were also higher under drier soil conditions. Current year seedlings had higher δ15N than saplings, particularly in P. latifolia, suggesting they exploit superficial soil layers. These results suggest that sprouts obtain benefit from resources stored in parent plants. At earlier stages, they perform better than seedlings. This response is not coupled to adult vulnerability to drought for these species, revealing the difficulty of predicting species dynamics during climate change.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: climate change; Drought; mediterranean forest; Nitrogen use; phillyrea latifolia; Quercus ilex; Recruitment; Regeneration; Seedling; sprouting; water use efficiency

Effects of disturbance caused by traditional Spanish rural land use on the regeneration of Cytisus multiflorus - Fernández-Santos, B; Gómez-Gutiérrez, J M; Moreno-Marcos, G (Applied Vegetation …, 1999)
. Cytisus multiflorus is a leguminous matorral shrub native to the NW Iberian Peninsula, where it is one of the most important species in the extension of matorral at the expense of set-aside agricultural land. Dehesas have traditionally been used for extensive livestock raising and matorral was periodically burnt, cut or pulled out. The two latter practices are now out of use. However, burning is more frequent than in the past. The effects of fire, cutting, and pulling out of C. multiflorus on its regeneration was studied in order to ascertain whether the presently increasing distribution of the species relates to firestimulated regeneration or to the reduction of other traditional practices. Three years after treatment two sets of parameters were determined: 1. Plant origin: seedlings and different ramet types ( ramets = resprout clumps), density, weight, and biomass as well as the percentage of resprouting. 2. Seed persistence at various soil depths. The possible mechanisms of breaking dormancy and plant emergence in different years after fire were studied in other experiments. The results suggest that the regeneration mechanism in C. multiflorus is stimulated by fire, but it is not an exclusive relationship. Stimulation occurs also after other disturbances leading to the total elimination of aerial biomass. The present expansion of the species does not appear to result from the abandonment of some traditional practices, such as cutting or pulling out, but from frequent fires (resulting in aerial-biomass elimination).
Keywords: Cutting; fire; Mediterranean shrubland; Pull-out; Ramet; seed bank; Seedling

Effects of disturbance caused by traditional Spanish rural land use on the regeneration of Cytisus multiflorus - Fernández-Santos, B.; Gómez-Gutiérrez, J. M.; Moreno-Marcos, G. (Applied Vegetation …, 1999)
. Cytisus multiflorus is a leguminous matorral shrub native to the NW Iberian Peninsula, where it is one of the most important species in the extension of matorral at the expense of set-aside agricultural land. Dehesas have traditionally been used for extensive livestock raising and matorral was periodically burnt, cut or pulled out. The two latter practices are now out of use. However, burning is more frequent than in the past. The effects of fire, cutting, and pulling out of C. multiflorus on its regeneration was studied in order to ascertain whether the presently increasing distribution of the species relates to firestimulated regeneration or to the reduction of other traditional practices. Three years after treatment two sets of parameters were determined: 1. Plant origin: seedlings and different ramet types ( ramets = resprout clumps), density, weight, and biomass as well as the percentage of resprouting. 2. Seed persistence at various soil depths. The possible mechanisms of breaking dormancy and plant emergence in different years after fire were studied in other experiments. The results suggest that the regeneration mechanism in C. multiflorus is stimulated by fire, but it is not an exclusive relationship. Stimulation occurs also after other disturbances leading to the total elimination of aerial biomass. The present expansion of the species does not appear to result from the abandonment of some traditional practices, such as cutting or pulling out, but from frequent fires (resulting in aerial-biomass elimination).
Keywords: Cutting; fire; Mediterranean shrubland; Pull-out; Ramet; seed bank; Seedling

Supervivencia y crecimiento de plántulas de encina en función de la intensidad de luz y la disponibilidad de agua - J.Ma, ESPELTA; RETANA, J; Riba, M (II Congreso Forestal Español, 1997)
The response of holm oak seedlings under a gradient of light and water av ail abilit y is analyzed. Seedling survival under all water levels decreased with increasing light. Conceming seedling morphology, both light and water availability changed biomass allocation to roots, stems and leaves, being light the most important source of variation
Keywords: Holm oak; light; Regeneration; Seedling; water

Vertebrate predation on Holm Oak, Quercus ilex, acorns in a fragmented habitat: effects on seedling recruitment - Santos, T.; Tellería, J. L. (Forest Ecology and Management, 1997)
Rodent and avian consumption of Holm Oak, Quercus ilex, acorns were examined in central Spain during two high-production seasons, 1990-1991 and 1993-1994, in 1 and 3 large stands and in 6 and 10 small stands (0.2-12 ha) respectively, to study the effects of vertebrate predation on seedling recruitment. Previous data indicate that wood mouse abundance is much higher in small stands. Tree size, frequency of acorn-bearing oaks and acorn abundance were similar in the two sizes of forest stands. Overall acorn consumption was 33.7 times higher in the small stands compared to that in the large stands in 1991, and 3.1 times larger in 1994. Consumption of acorns by mice in the small stands was 49 and 95 times greater than that by birds in the first and second year, respectively. Seedling recruitment was significantly higher in the large stands in both study seasons. Regeneration by ramets was roughly similar in small and large stands in both seasons. Thus, predation by mice was apparently responsible for the failure of sexual reproduction in the small stands. The results suggest that vegetative regeneration might be the prevalent reproductive method of Holm Oaks in small forest tracts.
Keywords: acorns; Forest fragmentation; oak; Seedling; Vertebrate predation

SUPERVIVENCIA DE PLANTULAS DE PINO CARRASCA (PINUS HALEPENSIS) y ENCINA (QUERCUS ILEX) EN BOSQUE MIXTOS DE AMBAS ESPECIES - ESPELTA, J M; RETANA, J; Gené, C; Riba, M (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
In this paper, survival of holm oak and Aleppo pine seedlings in holm oak stands, Aleppo pine stands and mixed stands, both in cut and uncut plots, is analized. Survival of holm oak seedlings in uncut plots is greater than that of Aleppo pine seedlings in the three types of forest considered. Mortality of seedlings of both species in 9ut plots is considerably smaller than that of uncut plots. K.W.:
Keywords: Aleppo pine; Holm oak; mixed forest; Seedling; survival curve

Etude de l'appareil radical de jeunes plants de Chênes verts dont le pivot se développe sans amputation, ni déviation - BEISSALAH, Y; AMIN, T; EL HAJZEIN, B; NEVILLE, P; BERNARD, Janine (Ann. For. Sci., 1988)
The experimental study of the root system of woody plants is far behind that of the aerial system. To make up for this difference, a study was begun on a Mediterranean sclerophyllous oak (Quercus ilex L.). The present study defines the developmental characteristics of the root system in young seedling whose tap root has neither been diverted nor amputated and which grows in different ecological conditions (substrates, temperatures). The results obtained can be used as an interpretative guide for the root system’s reactions to both diverting and amputating. These reactions will be described elsewhere. The study was made in R IEDACKER type minirhirotrons (1974) and L AMOND type fog chambers (1975). The root system of holly oak seedlings (fig. 1) consists of one main root (tap root) with positive geotropism and rapid and theoretically unlimited growth, from which thin, usually short, branch roots, either subhorizontal or oblique with slow, limited growth, spread out (fig. 5). The tap root is not rectilinear, but ondulates more or less regulary (fig. 1), both in loosely-packed substrates (peat ou loam) and in the absence of any substrate (fog chamber). The substrate’s resistance to root penetration, therefore, does not cause these ondulations. The largest branch roots generally begin growth on the convex part of the ondulation (fig. 1, B and C). The tap root grows better in peat than in loam or fog chambers (fig. 2). Its growth is subject to different types of fluctuations (fig. 4). It is highly sensitive to thermic variations (fig. 2 and 3). A 5 °C temperature drop (from 25 °C to 20 °C) decreases its growth rate by a quarter in peat and by half in loam (fig. 2). This decrease is lower in fog chambers because of their neutralizing effect. The tap root’s growth rate also fluctuates regardless of temperature, substrate (peat or loam), or lack of substrate (fig. 4). The fluctuation period varies from 2 to 7 days and is probably the expression of an irregular endogenetic rythm. Systematic ablation of branch roots as they appear has not effect on the variations in the tap root’s growth rate. Anatomy also differentiates the tap root from branch roots. The tap root usually has 6 major xylem fascicles (more rarely 4 to 8) directly underneath the cotyledons and connected to them in groups of three per cotyledon (fig. 6). Between these are often extra xylem fascicles which are smaller, connected to the epicotyle and disappear rapidly lower down (fig. 7, A and A’). The major xylem fascicles divide between the 3‘d and T&dquo; centimeter from the cotyledon by enlarging and isolating their wings (fig. 7, A and B) which can result at most in a tripling of the number of xylcm fascicles. These additional fascicles vanish progressively either by fusion and/or reduction up to the 20’&dquo; centimeter from the cotyledon (fig. 7, C). Beyond this, we find the same number of xylem fascicles as at the start, i.e. only major fascicles remain (fig. 7, D). The number of phloem fascicles, at first twice that of the major xylem fascicles in the area of the tap root near the cotyledons (fig. 7, A and B), decreases progressively, generally by fusion, until it equals the latter beyond the 20’&dquo; centimeter from the cotyledon (fig. 7, D). This remarkable fluctuation in fascicle number is probably related to the period of cotyledon influence. It is not present in the branch roots, which have between 3 and 5 xylem fascicles alternating with an equal number of phloem fascicles.
Keywords: development; Quercus ilex; rool; Seedling; Temperature; vascular bundles